Impacts of indoor environmental quality (IEQ) elements on residential property market: a review - Che Kasim, Asmma’ (Penerbit UTM Press, 2015)
Indoor environmental quality (IEQ) is among six criteria of Green Building Index (GBI) that need to be achieved by building owner in order to recognize their building as ‘green’ in Malaysia. The benefit of IEQ is to create conducive environment for human health. Besides influenced their overall image, leasing and resale value of the buildings, does indoor environmental quality (IEQ) features will give impact on real estate market in terms of price and rental particularly for residential building property? Therefore, this paper will review the broad literature regarding the impacts of indoor environmental quality (IEQ) for residential building property and its implication to towards property price and rental. The early hypothesis of this paper anticipates that indoor environmental quality (IEQ) features will indirectly increase residential property market price and rental. From this paper, it is hope that the positive impacts of these features will encourage building owners, developers and other main development actors to put these criteria into the same consideration as other criteria in GBI as one of the way to compensate the impact of the building towards economic, environment and social.